2014
DOI: 10.1371/journal.pone.0096006
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Sea Water Containing Selenium Provides Intestinal Protection against Duodenal Ulcers through the Upregulation of Bcl-2 and Thioredoxin Reductase 1

Abstract: Deep-sea water (DSW), which is rich in micronutrients and minerals and with antioxidant and anti-inflammatory qualities, may be developed as marine drugs to provide intestinal protection against duodenal ulcers. We determined several characteristics in the modified DSW. We explored duodenal pressure, oxygenation, microvascular blood flow, and changes in pH and oxidative redox potential (ORP) values within the stomach and duodenum in response to tap water (TW, hardness: 2.48 ppm), DSW600 (hardness: 600 ppm), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…DSW has received increasing attention for various beneficial characteristics, such as low temperature, nutrition, sterility, stability and safety (8)(9)(10). It is known that high atmospheric pressure contributes to small and stable water molecules, ionization state and easy absorption of DSW.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DSW has received increasing attention for various beneficial characteristics, such as low temperature, nutrition, sterility, stability and safety (8)(9)(10). It is known that high atmospheric pressure contributes to small and stable water molecules, ionization state and easy absorption of DSW.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have confirmed that DSW has pharmacological effects, including protecting the cardiovascular system (12,13), improving metabolic processes (14,15), anti-osteoporosis properties (16), treating atopic dermatitis skin lesions (17), accelerating recovery from physical fatigue (18), providing intestinal protection against duodenal ulcers (9) and inhibiting the metastatic potential of human breast cancer cell lines (19 Although DSW has already been studied for its alleviating fatigue effect in Wistar rats, the beneficial effects isolated in that study were only attributed to the minerals of DSW (20). In addition, the mechanism behind the beneficial effect has not yet been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…There are a lot of minerals, such as calcium (Ca), magnesium (Mg), vanadium (V), zinc (Zn), and potassium (K). Many studies have shown that DSW can be effectively used to treat diabetes, obesity, hyperlipidemia, and hypertension (Sheu et al 2013;Ha et al 2014b;Li et al 2014;Yang et al 2014). Mg supplementation improves myocardial metabolism and inhibits myocardial cell death.…”
Section: Introductionmentioning
confidence: 99%
“…The absorbed selenium is excreted through urine with some loss in sweat and skin and small amount though biliary, pancreatic and intestinal secretion. 8,9 Besides being an important nutrient, selenium has been identified as an antioxidant enzyme.…”
Section: Selenium Level In Plasma Ng/mlmentioning
confidence: 99%